Efficacy of Tree Species towards Gaseous Pollutants and its Significance in Air Pollution Control by Plantations of Pollution Resistant Trees - Bhattacharya, A. K. (Indian Forester, 1994)
Cultivation and conservation of certain fast growing resistant trees can be adopted as an effective and successful measure for the control of air pollution. Trees are sensitive as well as endowed with the power of absorbing the pollutants. Due to their such responses to the pollutants they can be used as indicators as well as scavangers of pollutants. Certain trees absorb and accumulate some gaseous, pollutants without being harmed and serve as a sink for these pollutants. A good number of tree species and varieties including some conifers and many angiosperms have successfully been found to withstand and mitigate air pollution hazards. Planting of trees as a measure for air pollution control has been implemented in many countries. The degree of tolerance towards the pollutants, varying within wide range, is controlled by many environmental and genetic factors, and hence some resistant tree varieties can be evolved through breeding, as has been done with respect to diseases. Therefore, certain fast growing trees with proven merits of abating gaseous pollutants must be grown in urban areas and around industries forming a belt, which will not only provide fuel and timber but also improve the ambient air quality and reduce air pollution.